2021
DOI: 10.1039/d1ta02833b
|View full text |Cite
|
Sign up to set email alerts
|

Well-defined Fe–Cu diatomic sites for efficient catalysis of CO2 electroreduction

Abstract: The diatomic catalysts (DACs) provide a new strategy for efficient catalysis of CO2 reduction reaction (CO2RR) owing to their maximum atomic utility and more flexible active sites. However, it is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 58 publications
3
78
0
Order By: Relevance
“…5c. 115 The tting results of EXAFS spectra (Fig. 5c) suggested the existence of Cu-Fe coordination.…”
Section: Bimetallic Sacsmentioning
confidence: 89%
“…5c. 115 The tting results of EXAFS spectra (Fig. 5c) suggested the existence of Cu-Fe coordination.…”
Section: Bimetallic Sacsmentioning
confidence: 89%
“…114 Additionally, as another further expansion of the SAC series, DACs introduce synergistic sites to distribute electrons, which can break the linear relationship of adsorption energies of different reaction intermediates. For instance, an Fe-Cu diatomic site with a unique coordination structure (FeN 4 -CuN 3 ) was precisely controlled by He et al 115 As shown in 119 They studied 28 SAAs, and found that about half of them selectively favor the CO 2 RR over the competing HER (Fig. 11h).…”
Section: Synergistic Single-atomic Catalysis In the Co 2 Rrmentioning
confidence: 99%
“…In addition, some works focused on combining Cu with other metals or metal oxides to break the scaling relations and contribute to highly selective CO formation at a decreased onset potential, which was caused by the balance between *COOH and *CO binding energies on the catalyst surface. Furthermore, CuAu, [ 68 ] CuPd, [ 69 ] CuZn, [ 70 ] CuCd, [ 71 ] CuFe, [ 72 ] In‐doped Cu@Cu 2 O, [ 73 ] and Cu/SnO x [ 74 ] had been studied to shift the main products to CO. Zn‐based materials have also been popular alternatives for ECR due to their abundant storage, low toxicity, and high CO selectivity. Woo's group reported a hierarchical hexagonal Zn catalyst, [ 75 ] which realized a highly efficient (FE CO,maximum = 95%) and stable performance (30 h) for CO production.…”
Section: Electrocatalysismentioning
confidence: 99%
“…In addition, some works focused on combining Cu with other metals or metal oxides to break the scaling relations and contribute to highly selective CO formation at a decreased onset potential, which was caused by the balance between *COOH and *CO binding energies on the catalyst surface. Furthermore, CuAu, [ 68 ] CuPd, [ 69 ] CuZn, [ 70 ] CuCd, [ 71 ] CuFe, [ 72 ] In‐doped Cu@Cu 2 O, [ 73 ] and Cu/SnO x [ 74 ] had been studied to shift the main products to CO.…”
Section: Electrocatalysismentioning
confidence: 99%